2009
DOI: 10.1021/es803368y
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Acropetal Translocation of Polycyclic Aromatic Hydrocarbons by Wheat (Triticum aestivum L.) Grown in Field-Contaminated Soil

Abstract: Uptake and acropetal translocation of 14 priority polycyclic aromatic hydrocarbons (PAHs) by wheat (Triticum aestivum L.) grown in 15 field-contaminated soils were investigated in a growth chamber. PAH concentrations in roots correlated positively with the corresponding concentrations in soils and negatively with the contents of soil organic carbon (p < 0.01). No clear linear relationship was found between log RCF (root concentration factor, µg g -1 root/µg g -1 soil on dry weight basis) and log K ow of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 23 publications
4
42
0
Order By: Relevance
“…The lipid concentration of wheat roots was found to be 2.18%. The RLOMAFs ranged from 1.05 to 4.55, which were higher than those of polybrominated diphenyl ethers (PBDEs, 0.02e0.71, Huang et al, 2011), but was similar to 4-ring polycyclic aromatic hydrocarbons (PAHs, 1.59e2.66, Tao et al, 2009). Yoo et al (2011) suggested that the transfer potential of long-chain PFCAs from soils to plants was lower than that of short-chain PFCAs.…”
Section: Uptake Of Pfaas By Wheat Rootsmentioning
confidence: 96%
See 3 more Smart Citations
“…The lipid concentration of wheat roots was found to be 2.18%. The RLOMAFs ranged from 1.05 to 4.55, which were higher than those of polybrominated diphenyl ethers (PBDEs, 0.02e0.71, Huang et al, 2011), but was similar to 4-ring polycyclic aromatic hydrocarbons (PAHs, 1.59e2.66, Tao et al, 2009). Yoo et al (2011) suggested that the transfer potential of long-chain PFCAs from soils to plants was lower than that of short-chain PFCAs.…”
Section: Uptake Of Pfaas By Wheat Rootsmentioning
confidence: 96%
“…Organic contaminants reach aerial plant organs in two ways: from the air and with the transpiration stream (Huang et al, 2010;Tao et al, 2009). It is possible that PFAAs in the soils evaporate into the ambient air and enter plants via gaseous uptake, contributing to their accumulation in the above-ground part of wheat, because PFAAs can be detected in the atmosphere (Li et al, 2011;Ahrens et al, 2011), though they do not readily volatize ).…”
Section: Distribution Patterns Of Pfaas In Wheatmentioning
confidence: 99%
See 2 more Smart Citations
“…Pahs include a variety family of more than 200 organic contaminants, most of which are carcinogenic and mutagenic [1].…”
Section: Olycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%